2015
DOI: 10.1038/srep13629
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing provides exquisite insight into the manipulation of the alveolar macrophage by tubercle bacilli

Abstract: Mycobacterium bovis, the agent of bovine tuberculosis, causes an estimated $3 billion annual losses to global agriculture due, in part, to the limitations of current diagnostics. Development of next-generation diagnostics requires a greater understanding of the interaction between the pathogen and the bovine host. Therefore, to explore the early response of the alveolar macrophage to infection, we report the first application of RNA-sequencing to define, in exquisite detail, the transcriptomes of M. bovis-infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
60
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 92 publications
9
60
0
Order By: Relevance
“…Previous studies have shown that bAM undergo extensive gene expression reprogramming following infection of M. bovis (Nalpas et al, 2015), with approximately one third of the genome significantly differentially expressed within bovine macrophages 24 hours after infection (Malone et al, 2018). Changes of this magnitude are comparable to those observed in previous experiments that have examined the chromatin remodelling that accompanies mycobacterial infection of macrophages, where trimethylation of lysine 4 of Histone H3 (H3K4me3) was shown to correlate with active transcription (Arts et al, 2018; Bouttier et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that bAM undergo extensive gene expression reprogramming following infection of M. bovis (Nalpas et al, 2015), with approximately one third of the genome significantly differentially expressed within bovine macrophages 24 hours after infection (Malone et al, 2018). Changes of this magnitude are comparable to those observed in previous experiments that have examined the chromatin remodelling that accompanies mycobacterial infection of macrophages, where trimethylation of lysine 4 of Histone H3 (H3K4me3) was shown to correlate with active transcription (Arts et al, 2018; Bouttier et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…( C ) Correlation and Venn diagram for both RNA-seq studies. The x-axis of the scatter plot represents the log 2 fold change for each of the 232 genes from this study and the y-axis represents the log 2 fold change for each of the 232 genes from the previous study (Nalpas et al, 2015). The Venn diagram shows the global overlap of differentially expressed genes from both studies with an FDR cut off of <0.1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mtb devoid of a capsule induced a strong pro-inflammatory response, and downregulated for example the expression of the IFNγ receptor, which could promote survival and persistence of Mtb [356,357]. Another study looking into the transcriptional response of bovine alveolar macrophages after M. bovis infection obtained conclusions different from other studies with similar settings, partly attributed to the use of detergent-free cultivated bacilli, but unfortunately a direct comparison of the transcriptomics upon infection of Mtb cultivated with or without detergent was not performed here [358]. Looking into the immunological response after BCG-vaccination and Mtb-challenge of mice, encapsulated BCG triggered a more potent immune response as compared to non-encapsulated (detergent-cultivated) BCG, featuring polyfunctional T cells, higher IFNγ production and lower CFU burden [359].…”
Section: Encapsulated Mtb Encapsulated Mtb Encapsulated Mtb Encapsulamentioning
confidence: 61%